NSTP National service training program - Punzalan, Michelle D.; Francisco, Virlyn S. (Manila, Philippines : Mindshapers Co. Inc., 2019)
This NSTP is essential component for the holistic development of the students since part of its main objective is to enhance health , leadership skills, sense of nationalism and patriotism.
Chapter 1. National Service training program -- Chapter 2. Contemporary Philippine Politics and government -- Chapter 3. Citizenship, Civil Society, and political participation -- Chapter 4. Leadership -- Chapter 5. Comprehensive Dangerous drugs act (R.A. 9165) -- Chapter 6. Health Education -- Chapter 7. First Aid Emergency response -- References.
Includes bibliographical references.
Keywords: MILITARY EDUCATION -- PHILIPPINES